Advantages and disadvantages of cantilever bridges - Bukhari, Meisan Ali; Fatani, Ola Hisham; Alrifai, Juman Alhusain; Kabli, Safa Wajdi; Alhomood, Manar Ali; Alnomani, Mona Hassan; Saber, Abdullah Musri Al Abu; Alghafis, Bayan Abdulaziz; Alkhalifah, Abdulaziz Musaad; Alghaythi, Khalid Shami; Alshaikh, Ali Bakr (International Journal Of Community Medicine And Public Health, 2021)
Utilizing cantilever bridges to perform fixed partial prostheses has been reported in the literature based on the increasing demands in this field to improve the outcomes and relieve extensive therapeutic approaches associated with complete oral rehabilitation. The current evidence indicates that cantilever bridges can effectively replace missing teeth with more favorable outcomes than removable partial dentures. However, evidence also shows that decreasing the number and size of cantilevered pontics and increasing abutment teeth are necessary to enhance the outcomes. Furthermore, if the occlusion is harmonious and stable, it has been demonstrated that cantilever bridges can be applied with the minimal periodontal ligament, which adds to its favorable outcomes. However, it should be noted that cantilever bridges are not applicable for all patients as it needs proper oral health status to be installed. Besides, it might also be associated with complications that may lead to failure. Therefore, further studies are still needed.